2011
DOI: 10.1038/ejhg.2010.159
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between the polymorphism of tumor necrosis factor-α-308 G>A and susceptibility to inflammatory bowel diseases and colorectal cancer: a meta-analysis

Abstract: Inflammatory bowel disease (IBD) and colorectal cancer (CRC) are common health problems worldwide. Tumor necrosis factor (TNF) is a type of cytokine that induces inflammation and inhibits tumorigenesis. Several studies have assessed the relationship between the polymorphism of TNF-a-308 G4A and the susceptibility to IBD and CRC; however, the results have been controversial. In addition, the hypothesis whether the increased risk of CRC in IBD patients could be partly ascribed to the polymorphism of TNF-a-308 G4… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
29
0

Year Published

2011
2011
2015
2015

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 42 publications
(34 citation statements)
references
References 35 publications
4
29
0
Order By: Relevance
“…As an important inflammatory factor, the polymorphisms in TNF-α gene have been largely studied, and TNF-α polymorphisms have been suggested to be associated with risks of many diseases, including rheumatoid arthritis, ankylosing spondylitis, and hepatitis B (Marcos et al, 2009;Postal et al, 2011). There are also many studies suggesting TNF-α polymorphisms are associated with risks of cancers, however, most them focus on the TNF-α -308 polymorphism (Fan et al, 2011;Wang et al, 2011). The relation between TNF-α -238 polymorphism and risk of cancer has not been well assessed.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…As an important inflammatory factor, the polymorphisms in TNF-α gene have been largely studied, and TNF-α polymorphisms have been suggested to be associated with risks of many diseases, including rheumatoid arthritis, ankylosing spondylitis, and hepatitis B (Marcos et al, 2009;Postal et al, 2011). There are also many studies suggesting TNF-α polymorphisms are associated with risks of cancers, however, most them focus on the TNF-α -308 polymorphism (Fan et al, 2011;Wang et al, 2011). The relation between TNF-α -238 polymorphism and risk of cancer has not been well assessed.…”
Section: Discussionmentioning
confidence: 99%
“…There are several common single nucleotide polymorphisms (SNP) in the TNF-α gene, including −238 (rs361525), −308 (rs1800629), −857 (rs1799724), and −1031 (rs1799964) positions, which could regulate TNF-α transcription and production (Qidwai et al, 2011). It has been well demonstrated that those SNPs can affect the functions of relevant proteins and further influence the host susceptibility to various cancers (Fan et al, 2011;Wang et al, 2011). Many epidemiological studies have evaluated the association between TNF-α 238 G/A polymorphism and hepatocellular carcinoma risk (Heneghan et al, 2003;Wang et al, 2003;Niro et al, 2005;Jeng et al, 2007;Kummee et al, 2007;Jeng et al, 2009;Wang et al, 2010b;Chen et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…Environmental factors including smoking, appendectomy, or endogenous microbiota have also been implicated in the onset of CD (Mondot et al, 2011). Recent studies have shown inconsistent results regarding the role of the TNF-α rs1800629 G>A polymorphism in the pathophysiology of CD (Fan et al, 2011;López-Hernández et al, 2014). Therefore, this meta-analysis was conducted to examine the associations between the TNF-α rs1800629 G>A and TNF-α rs1799724 C>T polymorphisms and CD susceptibility.…”
Section: Discussionmentioning
confidence: 99%
“…Some studies suggest that the TNF-α rs1800629 G>A and TNF-α rs1799724 C>T polymorphisms are not involved in CD susceptibility (Xie et al, 2012;López-Hernández et al, 2014). However, another study found a strong association between the TNF-α rs1800629 G>A polymorphism and susceptibility to CD (Fan et al, 2011). In order to resolve these conflicting results, we conducted the present meta-analysis to investigate the role of the TNF-α rs1800629 G>A and TNF-α rs1799724 C>T polymorphisms in CD susceptibility.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation